Folliculitis decalvans‐like pustular plaques on the limbs sparing the scalp. (17th October 2019) - Yang, Anes; Hannaford, Rodney; Kossard, Steven
Abstract: Folliculitis decalvans is a neutrophilic cicatricial alopecia characterised by progressive pustular folliculitis. Folliculitis decalvans is seen as a condition usually limited exclusively to the scalp and rarely affects the limbs. We present a case of a 63‐year‐old man with a 3‐year history of progressive pustular folliculitis with inflammatory patches and central scarring alopecia on both forearms and a circumscribed patch on his right lower leg. His presentation, clinical course and isolation of Staphylococcus aureus together with the histopathological findings all supported a folliculitis decalvans‐like pustular folliculitis limited to the limbs. Biopsies revealed follicular pustules, gross interfollicular fibrosis with plasma cells and concentric perifollicular fibrosis with lymphocytes, all features seen with folliculitis decalvans. The positive response to antibiotics combined with topical corticosteroids mirrored the response seen with scalp folliculitis decalvans. In contrast to the previously reported cases, the patient had no evidence of folliculitis decalvans on the scalp.